Strategi Pengelolaan Agroforestri Dusung Berkelanjutan di DAS Wai Batu Gajah: Pendekatan Berbasis SWOT (Sustainable Dusung Agroforestry Management Strategy in the Wai Batu Gajah Watershed: A SWOT-Based Approach) - Angela Martha Rettob; Regan Leonardus Kaswanto; Efi Yuliati Yovi (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2025)
As a form of traditional agroforestry, dusung provides numerous benefits regarding ecology, economy, and socio-culture in the Wai Batu Gajah Watershed in Ambon City, Maluku Province. The dusung management system is maintained by the local community and has become their traditional knowledge. It has the potential to support ecosystem sustainability. This research uses a SWOT approach to evaluate the internal and external factors influencing dusung agroforestry management and to develop priority strategies for sustainable management. The research was conducted in the upper part of the Wai Batu Gajah Watershed from September to October 2024. Data were collected through Focus Group Discussion (FGD) involving eight key informants representing the government sector, local communities (dusung owners), academics and religious leaders. Additionally, 30 dusung farmers were interviewed. Strategy analysis was carried out quantitatively using IFE, EFE, IE, SWOT, and QSPM matrices. The analysis results show that the internal factors score is 2.874 and the external factor score is 2.831. Therefore, the results of the xy axis combination place the position of dusung agroforestry in quadrant V, at the Hold and Maintain stage. The proposed priority strategy is to increase the effectiveness of strategic land through optimizing productive land, selecting superior seeds, using appropriate technology, and empowering farmers. Implementation of these strategies requires collaboration among the community, government, and private sector to support the sustainable management of dusung agroforestry. This study provides recommendations for policy development that support the sustainability of the Wai Batu Gajah Watershed ecosystem and improve community welfare.